Proctitis following stereotactic body radiation therapy for prostate cancer - Joh, Daniel Y.; Chen, Leonard N.; Porter, Gerald; Bhagat, Aditi; Sood, Sumit; Kim, Joy S.; Moures, Rudy; Yung, Thomas; Lei, Siyuan; Collins, Brian T.; Ju, Andrew Wenhua; Suy, Simeng; et al. (My University, 2014)
Background Proctitis after radiation therapy for prostate cancer remains an ongoing clinical challenge and critical quality of life issue. SBRT could minimize rectal toxicity by reducing the volume of rectum receiving high radiation doses and offers the potential radiobiologic benefits of hypofractionation. This study sought to evaluate the incidence and severity of proctitis following SBRT for prostate cancer. Methods Between February 2008 and July 2011, 269 men with clinically localized prostate cancer were treated definitively with SBRT monotherapy at Georgetown University Hospital. All patients were treated to 35-36.25Gy in 5 fractions delivered with the CyberKnife Radiosurgical System (Accuray). Rectal bleeding was recorded and scored using the CTCAE v.4. Telangiectasias were graded using the Vienna Rectoscopy Score (VRS). Proctitis was assessed via the Bowel domain of the Expanded Prostate Index Composite (EPIC)-26 at baseline and at 1, 3, 6, 9, 12, 18 and 24 months post-SBRT. Results The median age was 69 years with a median prostate volume of 39 cc. The median follow-up was 3.9 years with a minimum follow-up of two years. The 2-year actuarial incidence of late rectal bleeding ≥ grade 2 was 1.5%. Endoscopy revealed VRS Grade 2 rectal telangiectasias in 11% of patients. All proctitis symptoms increased at one month post-SBRT but returned to near-baseline with longer follow-up. The most bothersome symptoms were bowel urgency and frequency. At one month post-SBRT, 11.2% and 8.5% of patients reported a moderate to big problem with bowel urgency and frequency, respectively. The EPIC bowel summary scores declined transiently at 1 month and experienced a second, more protracted decline between 6 months and 18 months before returning to near-baseline at two years post-SBRT. Prior to treatment, 4.1% of men felt their bowel function was a moderate to big problem which increased to 11.5% one month post-SBRT but returned to near-baseline at two years post-SBRT. Conclusions In this single institution cohort, the rate and severity of proctitis observed following SBRT is low. QOL decreased on follow-up; however, our results compare favorably to those reported for patients treated with alternative radiation modalities. Future prospective randomized studies are needed to confirm these observations.
Keywords: Prostate cancer; SBRT; Rectal endoscopy; Telangiectasias; CyberKnife; Expanded prostate index composite; Bother; Proctitis; Rectal bleeding; Vienna rectoscopy score